2020
DOI: 10.3390/ijerph17051721
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of an Atrial Fibrillation Knowledge Assessment Tool (AFKAT)

Abstract: Assessing and improving public knowledge of atrial fibrillation (AF) could increase its detection rate and the subsequent use of stroke prevention therapies. However, there is no validated AF knowledge assessment tool applicable to the general population, including those at risk of AF. Therefore, we aimed to develop and validate such a tool. The tool was developed from a literature review and discussion with subject matter experts. Content validity was ensured by a ten-member panel of experts comprising cardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Moreover, 37% (19/52) of our participants were unaware that AFib could be symptomless. Even without symptoms, untreated AFib can result in stroke, underscoring the importance of educating those at risk about AFib-related complications (Jatau et al, 2020). Previous studies have found that individuals without palpitation symptoms and/or asymptomatic new-onset AFib have a 3.5-fold and 2.7-fold higher risk of cerebrovascular events than those with palpitations (Siontis et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, 37% (19/52) of our participants were unaware that AFib could be symptomless. Even without symptoms, untreated AFib can result in stroke, underscoring the importance of educating those at risk about AFib-related complications (Jatau et al, 2020). Previous studies have found that individuals without palpitation symptoms and/or asymptomatic new-onset AFib have a 3.5-fold and 2.7-fold higher risk of cerebrovascular events than those with palpitations (Siontis et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The Atrial Fibrillation Knowledge and Assessment Tool (AFKAT) was developed and validated for use in the general population and consists of 21 questions designed to assess knowledge of general AFib information, including risk factors, detection, prevention, and management (Jatau et al, 2020). For each item, one of three responses could be selected: "True," "False," or "I don't know."…”
Section: Instrumentmentioning
confidence: 99%
See 1 more Smart Citation
“…For the validation of items by focus groups or cognitive interviews, the literature discusses the possibility of involving either laypersons or people with background knowledge [ 58 , 59 ]. The focus groups in this study primarily involved people with no proven knowledge of the health care system, even though there was a high proportion of the chronically ill, who probably had greater system experience and probably also knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, corrected item-total correlations were tested. Two levels of inter-item correlations were suggested as acceptable: 0.2 ( 58 , 59 ) and 0.3 ( 60 , 61 ). We used the more liberal level of ≥0.2 in this study in order not to exclude some items on which some participants got high scores while others got low scores due to the heterogeneity within social demographic and health factors among subjects.…”
Section: Methodsmentioning
confidence: 99%